Relevansi Delimitasi Perbatasan Maritim Dengan Faktor Lingkungan - Evi Purwanti (Fakultas Hukum Universitas Pattimura, 2021)
Introductioan: This article discusses the relevance of maritime border delimitation with environmental factors that affect the determination of delimitation.Purposes of the Research: The purpose of this study is to analyze the urgency of the role of the environment in the maritime border delimitation process. Specifically focused on analyzing whether there is a positive relationship between environmental considerations and the development of the delimitation process and to determine the environmental factors that influence the delimitation.Methods of the Research: This research uses normative research with a conceptual approach. Researchers use relevant environmental law concepts in the maritime border delimitation process.Results of the Research: The results of the study show that there is a relevance of environmental factors in determining maritime border delimitation, among others from factors: conservation of wildlife reserves, the principle of natural prolongation, the principle of sustainable development, mineral resources, and fisheries. The relationship between environmental factors and the delimitation process occurs in two ways: First, environmental considerations show a direct influence in the selection of the delimitation method. Here environmental factors are an important motive in the delimitation process. Second, environmental factors affect the delimitation process indirectly where there are a number of delimitation agreements that do not include specific provisions regarding the environment, but the evidence shows that the parties are motivated by environmental factors in negotiating delimitation.